Implementasi Kurva Lissajous Dalam Desain Motif Batik Geometris Pada Media Busana Rompi Bernilai Seni dan Terukur Matematis - Hilman Atohar; Abdur Rohim; Khafidhoh Nurul Aini (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Mathematics learning often faces challenges in visualizing abstract concepts such as parametric curves. One of them is the Lissajous curve, which is difficult for students to understand without visual aids. This study aims to develop a visual media in the form of a geometrically patterned batik vest inspired by the Lissajous curve as a creative and applicable mathematics learning media that is both artistically valuable and mathematically measurable. This research uses the Research & Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), restricted up to the development stage. Data analysis techniques use expert validation to assess the feasibility of the media. Three experts participated as validators: a mathematics material expert, a batik design expert, and a learning media expert. The validation results showed that the mathematics material expert gave a percentage of 87.5% (very feasible), the batik design expert gave 90% (very feasible), and the learning media expert gave 90% (very feasible), with an average of 89.17% (very feasible). The results of this study produced a batik vest that is not only aesthetically high-value but also mathematically measurable, with three parametric equation models applied through gold embroidery techniques on black fabric. Thus, the product is declared feasible to be used as an innovative mathematics learning medium.